Authoritative Parenting and Moral Development: A Quantitative Study in Rural Indonesia - Lubis, Salsa Nabila; Nashrillah, Nashrillah (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2024)
This study investigated the influence of parenting styles on children's moral behavior in Pidoli Lombang Village, Panyabungan District, Mandailing Natal Regency, Indonesia. A quantitative approach using a survey method was employed, with a sample of 30 children aged 7 to 12 years selected through random sampling. Data were collected using questionnaires distributed to the children's parents or guardians, which assessed parenting styles (authoritative, authoritarian, and permissive) and children's moral behavior. Validity and reliability tests were conducted to ensure data quality. Prerequisite tests, including the Kolmogorov-Smirnov normality test and Levene's test for homogeneity of variances, were performed before the main analysis. Descriptive statistics revealed that authoritative parenting was the most predominantly practiced style in the village. A simple linear regression analysis showed a significant positive relationship between authoritative parenting and children's moral behavior, while authoritarian and permissive parenting styles exhibited negative relationships. The findings suggest that a balanced approach to parenting, combining discipline with emotional support, positively contributes to children's moral development. The study highlights the importance of implementing authoritative parenting in shaping positive moral behavior in children and provides valuable insights for parents, educators, and policymakers in fostering responsible ethical behavior in children within the context of rural Indonesian communities.